Racial Differences by Ischemic Stroke Subtype: A Comprehensive Diagnostic Approach. (7th May 2012) - Song, Sarah; Burgess, Richard E.; Kidwell, Chelsea S.
Abstract : Background . Previous studies have suggested that black populations have more small-vessel and fewer cardioembolic strokes. We sought to analyze racial differences in ischemic stroke subtype employing a comprehensive diagnostic workup with magnetic resonance-imaging-(MRI-) based evaluation including diffusion-weighted imaging (DWI). Methods . 350 acute ischemic stroke patients admitted to an urban hospital with standardized comprehensive diagnostic evaluations were retrospectively analyzed. Ischemic stroke subtype was determined by three Trial of Org 10172 in Acute Stroke Treatment (TOAST) classification systems. Results . We found similar proportions of cardioembolic and lacunar strokes in the black and white cohort. The only subtype category with a significant difference by race was "stroke of other etiology, " more common in whites. Black stroke patients were more likely to have an incomplete evaluation, but this did not reach significance. Conclusions . We found similar proportions by race of cardioembolic and lacunar strokes when employing a full diagnostic evaluation including DWI MRI. The relatively high rate of cardioembolism may have been underappreciated in black stroke patients when employing a CT approach to stroke subtype diagnosis. Further research is required to better understand the racial differences in frequency of "stroke of other etiology" and explore disparities in the extent of diagnostic evaluations.